Carbon nanotube / resin composite material based on acoustic resonance mixing and preparation method thereof
By utilizing acoustic resonance mixing technology and the shear effect of spherical materials, the problems of uneven mixing and weak interfacial bonding in single-walled carbon nanotube/thermoplastic resin composites have been solved, enabling the preparation of high-performance composite materials suitable for automotive parts and electronic housings.
Patent Information
- Application Number
- CN202511406554.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-09-29
Smart Images

Figure CN120904706A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of nanotube composites, and particularly to a carbon nanotube / resin composite based on acoustic resonance mixing and a preparation method thereof. BACKGROUND
[0002] Single-walled carbon nanotubes (SWCNTs) as a one-dimensional nanometer reinforcing material have extremely high mechanical strength (tensile strength up to several hundred GPa), excellent thermal conductivity (thermal conductivity coefficient 2000-6000 W / m·K) and electrical properties (including high conductivity, which can form a continuous conductive network to impart antistatic properties), and are widely used in resin composites to improve mechanical, thermal, antistatic and functional properties. Thermoplastic resin is an engineering resin that is widely used in the automotive, electronics and mechanical fields due to its good mechanical strength, heat resistance and processability. However, in the prior art, when single-walled carbon nanotubes are added to thermoplastic resin and other auxiliary materials, due to differences in material quality, density and performance, the finished product is prone to uneven mixing, agglomeration or phase separation.
[0003] Currently, the main preparation methods for single-walled carbon nanotube / thermoplastic resin composites include mechanical stirring, melt blending and solution mixing. Mechanical stirring methods such as high-speed shearing or ball milling, although simple, often result in stratification due to differences in material density and affinity, incomplete dispersion, long processing time (several hours), and the introduction of defects (such as SWCNTs breaking), resulting in only a 10-20% improvement in tensile strength of the composite, limited improvement in thermal conductivity coefficient (<30%), and insignificant antistatic performance (surface resistivity reduction of less than 2 orders of magnitude). The melt blending method uses a twin-screw extruder, but if the pre-mixing is uneven, it can cause blockage or performance fluctuations during extrusion, and is suitable for low filling amounts (<1 wt%), and high filling amounts can easily cause agglomeration, making it difficult to form an effective conductive network to achieve excellent antistatic properties. The solution mixing method requires an organic solvent, which can affect the environment and the purity of the finished product, and the drying process is complex. All of the above methods, combined with the limitations of multiple types of raw materials and ratios, have low efficiency, narrow application range (limited to similar density materials), poor scalability, and the risk of damaging the integrity of the materials, which can affect the performance and consistency of the final composite (including the difficulty of achieving stable antistatic performance), limiting the potential of the composite in high-end applications. SUMMARY
[0004] In order to overcome the disadvantages of the prior art in preparing single-walled carbon nanotube / thermoplastic resin composite materials, due to the limitations of the technology, as described in the background art, the present application provides a method for realizing the uniform dispersion and interface wetting of multi-component materials with large density difference and different performance (such as conductivity and insulation) on a microscale by using relevant materials and the shearing effect of spherical materials through acoustic resonance technology, solving the problems of uneven dispersion of raw materials, weak interface combination and performance degradation in the mixing process of traditional technology, and the prepared composite material product has excellent mechanical properties, thermal conductivity and anti-static performance, and is particularly suitable for carbon nanotube / resin composite materials based on acoustic resonance mixing and preparation methods for applications in the fields of automobile parts, electronic housings and the like.
[0005] The technical solution adopted by the present application to solve its technical problems is: The carbon nanotube / resin composite material based on acoustic resonance mixing comprises single-walled carbon nanotubes, glass fibers, carbon fibers, spherical nanosilica and thermoplastic resin powder components; the content of the single-walled carbon nanotubes is 0.5-5wt%, the glass fibers are 1-10wt%, the carbon fibers are 0.5-5wt%, the spherical nanosilica is 0.1-2wt%, and the thermoplastic resin powder is 78-97.9wt%; the preparation method of the carbon nanotube / resin composite material based on acoustic resonance mixing comprises the following processes, S1: preparing single-walled carbon nanotubes, thermoplastic resin powder, glass fibers, carbon fibers and spherical nanosilica according to the quantities, and modifying and pre-drying the surfaces of the glass fibers and the spherical nanosilica; S2: putting the materials in step S1 into the mixing chamber of an acoustic resonance mixing device, and performing multi-stage acoustic resonance mixing of the materials, the resonance cavity of the resonance mixing device generates a resonance frequency of 50-70Hz and an acceleration of 5-100g, a standing wave field is formed in the mixing chamber to realize micro-uniform dispersion of the multiple components, and the dispersion uniformity is >96%; S3: after mixing, the material is vacuum degassed through a vacuum degassing device, hot-pressed into a preform through a hot-pressing device, dried through a vacuum drying device, and extruded into a shape through a double-screw extruder, to obtain a carbon nanotube / resin composite material.
[0006] Further, the thermoplastic resin powder is one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer, polymethyl methacrylate, polyamide, polycarbonate, polyformaldehyde, polybutylene terephthalate, polyethylene terephthalate, polyether ether ketone, polyimide, polyphenylene sulfide, polyether sulfone, polytetrafluoroethylene, polysulfone, polymethyl pentene, ethylene-vinyl acetate copolymer, and polyphthalamide, and the density is 1.0g / cm³-1.4g / cm³.
[0007] Further, the single-walled carbon nanotube has a purity of >80%, a diameter of 0.5nm-2nm, a length of 1μm-100μm, and a density of 1g / cm³-1.8g / cm³; the glass fiber has a density of 2g / cm³-2.6g / cm³ and a length of 1mm-10mm; the carbon fiber has a density of 1.2g / cm³-1.9g / cm³ and a length of 0.5mm-5mm; and the spherical nanosilica has a density of 1.6g / cm³-2.3g / cm³ and a particle size of 100nm-200nm.
[0008] Further, in the step S1, the surfaces of the glass fiber and the spherical nanosilica are modified by a silane coupling agent treatment, and the modification is achieved by stirring the glass fiber and the spherical nanosilica in a stirrer at room temperature for 20-40 minutes, and the pre-drying is performed in a drying device at 75°C-85°C for 2-2.5 hours.
[0009] Further, in the multi-stage acoustic resonance mixing of the step S2, the first stage is mixed at an acceleration of 30g-80g for 8-12 minutes, and the second stage is mixed at an acceleration of 60g-95g for 2-8 minutes, and the total mixing time is <40 minutes.
[0010] Further, in the step S3, the vacuum degree of the vacuum degassing device is -0.1MPa--0.2MPa, and the time is 15-25 minutes; the pressure of the hot-pressing device is 5MPa-6MPa, the temperature is 150°C-160°C, and the time is 10-15 minutes; the drying temperature of the vacuum device is 60°C-65°C, and the drying time is 60-70 minutes; and the tensile strength of the carbon nanotube / resin composite material is >90MPa, the Young's modulus is >4GPa, the thermal conductivity is >0.5W / m•K, and the surface resistivity is 1.0×10^4-1.0×10^9Ω / sq.
[0011] Further, in the step S2, the acoustic resonance mixing device comprises a resonance cavity, an acoustic wave frequency modulation module, a mixing chamber, a control module, and a fixing device, the resonance cavity is installed in the middle of the shell by the fixing device, the acoustic wave frequency modulation module is installed at the lower end of the resonance cavity, the mixing chamber is installed in the resonance cavity, the control module is installed at the front end of the shell, the power output end of the control module and the power input end of the acoustic wave frequency modulation module are connected to the lower inside of the acoustic wave frequency modulation module through wires, the vacuum degassing device is installed at the back of the resonance cavity, the air inlet pipe of the vacuum degassing device and the air outlet pipe at the upper end of the mixing chamber are connected through a pipeline, the front end of the shell has a sealed soundproof door, the sealed door is opened before mixing to put raw materials into the mixing chamber and closed.
[0012] Further, in the step S2, the sound wave frequency modulation module of the applied acoustic resonance mixing device can output different frequency signals to the resonance cavity through the frequency automatic regulator under the action of the control module, the resonance cavity can generate a low-frequency standing wave field to act on the mixing chamber, realizing the acoustic flow and uniform mixing of multi-component raw materials without damaging the physical structure of the materials.
[0013] Further, in the step S2, the resonance sound wave formed by the low-frequency standing wave field can realize the preferential solution of the agglomeration and interface fusion of raw material components with a density difference greater than 30% through the shear effect of the spherical components, without the need for additional dispersants, and the purity is greater than 99%.
[0014] Compared with the prior art, the present application has the following advantages: the present application is aimed at the preparation of traditional single-walled carbon nanotube (SWCNTs) / thermoplastic resin composite materials, and the problems of uneven dispersion, weak interface bonding and performance degradation caused by the easy agglomeration of SWCNTs. The finished product prepared by the acoustic resonance mixing device cooperates with the spherical components, and the tensile strength is improved by 70%, the thermal conductivity coefficient is more than 80%, the surface resistivity is reduced by 7-10 orders of magnitude, and the finished product has excellent mechanical properties, thermal conductivity and anti-static properties, and is especially suitable for high application in automobile parts, electronic shells and other fields. In summary, the present application has good application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0015] Figure 1 is the scanning electron microscope (SEM) image of the composite material prepared by the acoustic resonance mixing device of the present application. DETAILED DESCRIPTION
[0016] The carbon nanotube / resin composite based on acoustic resonance mixing comprises single-walled carbon nanotubes, glass fibers, carbon fibers, spherical nanosilica and thermoplastic resin powder components; the content of the single-walled carbon nanotubes is 0.5-5 wt%, the content of the glass fibers is 1-10 wt%, the content of the carbon fibers is 0.5-5 wt%, the content of the spherical nanosilica is 0.1-2 wt%, and the content of the thermoplastic resin powder is 78-97.9 wt%. The thermoplastic resin powder is one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer, polymethyl methacrylate, polyamide, polycarbonate, polyformaldehyde, polybutylene terephthalate, polyethylene terephthalate, polyether ether ketone, polyimide, polyphenylene sulfide, polyether sulfone, polytetrafluoroethylene, polysulfone, polymethyl pentene, ethylene-vinyl acetate copolymer, and polyphthalamide, mixed, with a density of 1.0 g / cm3-1.4 g / cm3; the single-walled carbon nanotubes have a purity of >80%, a diameter of 0.5 nm-2 nm, a length of 1 μm-100 μm, and a density of 1 g / cm3-1.8 g / cm3; the glass fibers have a density of 2 g / cm3-2.6 g / cm3 and a length of 1 mm-10 mm; the carbon fibers have a density of 1.2 g / cm3-1.9 g / cm3 and a length of 0.5 mm-5 mm; and the spherical nanosilica has a density of 1.6 g / cm3-2.3 g / cm3 and a particle size of 100 nm-200 nm.
[0017] After the acoustic resonance synergistic spherical silica mixing treatment, the single-walled carbon nanotubes can be uniformly dispersed in the thermoplastic resin matrix to construct a 3D network structure, which is conducive to forming a continuous mechanical reinforcing network, a heat conduction path and an electric conduction network, and achieving excellent mechanical properties, heat conduction properties and anti-static properties.
[0018] The preparation method of carbon nanotube / resin composite material based on acoustic resonance mixing, the working principle is that the low frequency vibration of 50-70 Hz is generated in the acoustic wave frequency modulation module, the standing wave field is formed in the mixing chamber through the resonance cavity, the mechanical resonance and energy superposition are applied to the multi-component materials with large density and performance difference to generate large amplitude vibration, the contents in the mixing chamber are compressed to generate acoustic flow, the whole material is fully fluidized, the single-walled carbon nanotube is de-agglomerated and uniformly mixed with thermoplastic resin powder and other raw materials, and the damage and unevenness of the traditional method are avoided. The process includes the following steps: (1) preparing single-walled carbon nanotubes, thermoplastic resin powder, glass fiber, carbon fiber and spherical nanometer silicon dioxide according to the quantity, and modifying the surface of glass fiber and spherical nanometer silicon dioxide (the density of spherical nanometer silicon dioxide is about 2.2 g / cm³, which is used as an interface modifier to promote filler dispersion, increase fluidity and provide shear force to de-agglomerate, improve the interface bonding of fiber / nanoparticle and resin matrix, enhance dispersion and compatibility, prevent agglomeration, and improve the overall mechanical, electrical and thermal properties of the composite material), and pre-drying; specifically, the surface of glass fiber and spherical nanometer silicon dioxide is modified by silane coupling agent treatment, the modification is realized by stirring glass fiber, spherical nanometer silicon dioxide and silane coupling agent in a stirrer at room temperature for 20-40 minutes, and the pre-drying is carried out in a drying equipment at 75°C-85°C for 2-2.5 hours. (2) Put the materials in step S1 into the mixing chamber of the acoustic resonance mixing device, and carry out multi-stage acoustic resonance mixing of multiple materials, the resonance cavity of the resonance mixing device generates resonance frequency of 50-70 Hz and acceleration of 5-100 g, and standing wave field is formed in the mixing chamber to realize micro-uniform dispersion of multiple components, and the dispersion uniformity is >96%; in the multi-stage acoustic resonance mixing, the first stage is mixed at an acceleration of 30g-80g for 8-12 minutes, the second stage is mixed at an acceleration of 60g-95g for 2-8 minutes, and the total mixing time is <40 minutes.(3): the mixed material is subjected to vacuum degassing device, vacuum degassing (to remove dissolved gas (such as air, hydrogen, oxygen) and bubbles in the mixed material, to prevent the formation of voids, cracks or defects in the subsequent processing, thereby improving the density, mechanical strength and overall integrity of the composite material), hot pressing equipment hot pressing preforming (hot pressing combines pressure and temperature to promote particle rearrangement, plastic flow and resin curing), vacuum drying equipment drying and double screw extrusion molding to obtain carbon nanotube / resin composite material; specifically, the vacuum degree of the vacuum degassing device is -0.1 MPa--0.2 MPa, and the time is 15 minutes-25 minutes; the pressure of the hot pressing equipment is 5 MPa-6 MPa, the temperature is 150°C-160°C, and the time is 10 minutes-15 minutes; the material temperature of the vacuum drying equipment is 60°C-65°C, and the drying time is 60 minutes-70 minutes; the tensile strength of the carbon nanotube / resin composite material is >90 MPa, the Young's modulus is >4 GPa, the thermal conductivity is >0.5 W / m•K, and the surface resistivity is 1.0×10^4-1.0×10^9Ω / sq; the applied acoustic resonance mixing equipment includes a resonance cavity (transmits vibration signals of the acoustic frequency modulation module), an acoustic frequency modulation module (outputs vibration signals of different functional frequencies to the resonance cavity), a mixing chamber (mixes materials), a control module (controls the size of the vibration signal output by the acoustic frequency modulation module), and a fixing device (fixes the function), the resonance cavity is installed in the middle of the shell through the fixing device, the acoustic frequency modulation module is installed at the lower end of the resonance cavity, the mixing chamber is installed in the resonance cavity, the control module is installed at the front end of the shell, the power output end of the control module and the power input end of the acoustic frequency modulation module are connected below the acoustic frequency modulation module, the vacuum degassing device is installed at the back of the resonance cavity, the air inlet pipe of the vacuum degassing device and the exhaust pipe at the upper end of the mixing chamber are connected through the pipeline, the front end of the shell has a sealed soundproof door, the sealed door is opened before mixing to put raw materials into the mixing chamber and closed. The acoustic frequency modulation module of the applied acoustic resonance mixing equipment can output different frequency signals to the resonance cavity through its own frequency automatic adjuster under the action of the control module, the resonance cavity can generate a low-frequency standing wave field to act on the mixing chamber, realizing the acoustic flow and uniform mixing of multi-component raw material, without damaging the physical structure of the material. The resonant acoustic waves formed by the low-frequency standing wave field can realize the preferential solution of the agglomeration and interface fusion of raw material components with a density difference greater than 30%, without the need for additional dispersants, maintaining a purity of greater than 99%.
[0019] Figure 1For the SEM image of the composite material of the present application, it can be seen that the single-walled carbon nanotubes are uniformly dispersed in the thermoplastic resin matrix after the acoustic resonance mixing treatment, showing a 3D network structure, which is beneficial to the formation of a continuous mechanical reinforcing network, a heat conduction path and an electrically conductive network, realizing excellent mechanical properties, heat conduction properties and anti-static properties. In Examples 1-4 and Comparative Examples 1-2 below, the screw diameter of the extruder is 25 mm, L / D = 40, the temperature is 180-280°C, the rotation speed is 80-250 rpm, the extrusion molding is a standard sample, the mechanical properties are tested using a universal material testing machine (ASTM D638 standard, tensile speed 5 mm / min), the heat conduction properties are tested using a laser flash method (ASTM E1461 standard), and the anti-static properties are tested using a surface resistivity four-probe method (ASTM D257 standard).
[0020] Example 1: (1) Take single-walled carbon nanotube powder 0.5wt% (relative to the mass of PP), glass fiber 2wt%, carbon fiber 0.5wt%, spherical nanosilica 0.2wt% and PP powder (thermoplastic resin powder), total mass 100g for standby. (2) Modify the surface of the glass fiber and spherical nanosilica (specifically, the surface of the glass fiber and spherical nanosilica is modified by silane coupling agent treatment) and pre-dry. (3) Place the above materials in the mixing chamber of the acoustic resonance mixing device, start the device, set the acceleration to a low level of 30g, mix for 8 minutes in the first stage, and adjust the acceleration to 60g for 2 minutes in the second stage. (4) After mixing, the material is vacuum degassed, hot-pressed preformed and vacuum dried, Figure 1 It can be seen that SEM observation shows that each component is uniformly distributed in the PP component without agglomeration. (5) The carbon nanotube / resin composite material obtained after the above material is extruded by a twin-screw extruder, and the test performance results are as follows: tensile strength is 87 MPa (pure PP is 55 MPa, increased by 58%), Young's modulus is 2.9 GPa (pure PP is 1.8 GPa, increased by 61%), thermal conductivity is 0.34 W / m·K (pure PP is 0.20 W / m·K, increased by 70%), and surface resistivity is 1.0×10^9Ω / sq (pure PP is 1.0×10^15Ω / sq, decreased by 6 orders of magnitude). This example proves that acoustic resonance mixing can effectively treat materials with different densities and different properties, which is suitable for low-reinforced composite applications and initially gives anti-static properties.
[0021] Example 2: (1) Take single-walled carbon nanotube powder 1wt%, glass fiber 4wt%, carbon fiber 1wt%, spherical nanosilica 0.5wt% and PP powder, total mass 200g. (2) Modify the surface of glass fiber and spherical nanosilica (specifically, the surface of glass fiber and spherical nanosilica is modified by silane coupling agent treatment) and pre-dry. (3) Put the above materials into the mixing chamber of the acoustic resonance mixing device, start the device, set the acceleration to medium level 50g, first stage mixing 10 minutes, second stage increase the acceleration to 60g mixing 5 minutes. (4) After mixing, the material is vacuum degassed, hot-pressed preformed and vacuum dried, and the material is uniformly fused. (5) The carbon nanotube / resin composite material obtained after the above material is extruded by a double screw extruder, and the test performance results are as follows: tensile strength 95MPa (increased by 73%), Young's modulus 3.6GPa (increased by 100%), thermal conductivity coefficient 0.45W / m·K (increased by 125%), surface resistivity 1.0×10^7Ω / sq (pure PP is 1.0×10^15Ω / sq, reduced by 8 orders of magnitude). The data logic shows that with the increase of the filling amount, the performance improvement shows a linear trend (correlation coefficient R²=0.97), which is attributed to the uniform dispersion of acoustic resonance avoiding stress concentration caused by agglomeration. This example is suitable for electronic shell material applications with medium strength requirements, and provides significant anti-static performance.
[0022] Example 3: Preparation and performance test of high filling amount carbon nanotube / resin composite based on acoustic resonance mixing. (1) Take single-walled carbon nanotube powder 3wt%, glass fiber 8wt%, carbon fiber 3wt%, spherical nanosilica 1wt% and PP powder, total mass 500g. (2) Modify the surface of glass fiber and spherical nanosilica (specifically, the surface of glass fiber and spherical nanosilica is modified by silane coupling agent treatment) and pre-dry. (3) Put the above materials into the mixing chamber of the acoustic resonance mixing device, start the device, set the acoustic resonance mixing acceleration intensity to high level 80g, mix for 12 minutes in the first stage, adjust to 95g for 8 minutes in the second stage, after mixing, the material is vacuum degassed, hot-pressed preformed and vacuum dried, although the density difference leads to easy stratification in traditional methods, but acoustic resonance achieves >98% uniformity (the distribution is verified by X-ray CT scanning). (5) The carbon nanotube / resin composite material obtained after the above material is extruded by double screw extruder, the performance test results are as follows: tensile strength is 100MPa (increased by 82%), Young's modulus is 4.3GPa (increased by 139%), thermal conductivity is 0.58W / m·K (increased by 190%), surface resistivity is 1.0×10^4Ω / sq (pure PP is 1.0×10^15Ω / sq, reduced by 11 orders of magnitude), the performance data is positively correlated with the filling amount, but the growth rate slows down (threshold effect), which proves the robustness of the technology under high filling, this example is suitable for automotive parts applications with high heat management requirements, and gives excellent anti-static and conductive network.
[0023] Example 4: (1) Take single-walled carbon nanotube powder 1.5wt% (relative to the mass of PP), glass fiber 5wt%, carbon fiber 1.5wt%, spherical nanosilica 0.6wt%, and PP powder, total mass 200g. (2) Modify and pre-dry the surface of the glass fiber and spherical nanosilica (specifically, the surface of the glass fiber and spherical nanosilica is modified by silane coupling agent treatment). (3) Place the above materials in the mixing chamber of the acoustic resonance mixing device, start the device, set the acceleration to medium level 50g, mix for 10 minutes in the first stage, and increase to 60g for 5 minutes in the second stage. (4) After mixing, the material is vacuum degassed, hot-pressed preformed, and vacuum dried, and the material is uniformly fused. (5) The carbon nanotube / resin composite material obtained after the above material is extruded by a double screw extruder, and the test performance results are as follows: tensile strength is 93MPa (pure PP is 55MPa, increased by 69%), Young's modulus is 3.7GPa (pure PP is 1.8GPa, increased by 106%), thermal conductivity is 0.47W / m·K (pure PP is 0.20W / m·K, increased by 135%), and surface resistivity is measured by four-probe method (ASTM D257 standard) 1.0×10^6Ω / sq (pure PP is 1.0×10^15Ω / sq, decreased by 9 orders of magnitude). Compared with Example 2, this example further strengthens the formation of the conductive network by optimizing the ratio of carbon nanotubes and fibers, and the antistatic performance is improved by 1 order of magnitude, while the mechanical and thermal conductivity indicators remain at a high level. This example proves that the acoustic resonance mixing and spherical nanosilica can efficiently construct a continuous conductive path, and is suitable for electronic packaging and precision instrument shell fields.
[0024] Comparative Example 1: Two kinds of finished composite materials were obtained by using the same materials (1 wt% single-walled carbon nanotubes + 4 wt% glass fibers + 1 wt% carbon fibers + 0.5 wt% spherical nano-silica + PP, total mass 100 g) and then pre-mixed by acoustic resonance mixing (acceleration 30 g, first stage 10 minutes, second stage 5 minutes, including full set of pretreatment and post-treatment) and traditional high-speed stirring (speed 5000 rpm, 40 minutes) respectively before extrusion. The data obtained are as follows: the acoustic resonance sample has a tensile strength of 90 MPa, a Young's modulus of 3.6 GPa (pure PP is 1.8 GPa, an increase of 100%), a thermal conductivity of 0.48 W / m-K, and a surface resistivity of 1.0 x 10^7 Ω / sq (pure PP is 1.0 x 10^15 Ω / sq, a decrease of 8 orders of magnitude); the traditional sample has a tensile strength of 70 MPa (an increase of 27%), a Young's modulus of 2.4 GPa (pure PP is 1.8 GPa, an increase of 33%), a thermal conductivity of 0.30 W / m-K (an increase of 50%), and a surface resistivity of 1.0 x 10^10 Ω / sq (pure PP is 1.0 x 10^15 Ω / sq, a decrease of 5 orders of magnitude). The differences between the two are attributed to the acoustic flow of acoustic resonance, which can better handle the performance heterogeneity of the materials and avoid damage. This example logically proves the superiority of the present application, including significant improvement in anti-static performance.
[0025] Comparative Example 2: (1) Take 1wt% single-walled carbon nanotube powder (relative to the mass of PP), 4wt% glass fiber, 1wt% carbon fiber and PP powder (without adding spherical nanosilica), the total mass is 200g. (2) Modify the surface of the glass fiber (specifically, the surface of the glass fiber is modified by silane coupling agent treatment) and pre-dry. (3) Put the above materials in the mixing chamber of the acoustic resonance mixing device, start the device, set the acceleration to medium level 50g, mix for 10 minutes in the first stage, and increase the acceleration to 60g in the second stage for 5 minutes. (4) After mixing, the material is vacuum degassed, hot-pressed preformed and vacuum dried, and it is observed that the material fusion is basically uniform, but SEM shows that there is a slight agglomeration of carbon nanotubes and fibers between the PP particles. (5) The carbon nanotube / resin composite material obtained after the above material is extruded by a double screw extruder, and the test performance results are as follows: tensile strength is 78MPa (pure PP is 55MPa, increased by 42%), Young's modulus is 2.7GPa (pure PP is 1.8GPa, increased by 50%), thermal conductivity is 0.32W / m·K (pure PP is 0.20W / m·K, increased by 60%), and surface resistivity is 1.0×10^9Ω / sq (pure PP is 1.0×10^15Ω / sq, reduced by 6 orders of magnitude). Compared with Example 2, the performance improvement of this comparative example is significantly reduced (tensile strength is reduced by 18%, Young's modulus is reduced by 25%, thermal conductivity is reduced by 29%, and surface resistivity is reduced by 2 orders of magnitude), which proves that the use of acoustic resonance mixing alone can improve the dispersion, but the lack of spherical nanosilica as a dispersion aid cannot fully inhibit the agglomeration, resulting in incomplete conductive network and heat conduction path, and the lack of synergistic effect. The logic of this comparative example shows that spherical nanosilica is a key synergistic component to achieve high performance, which is suitable for verifying the importance of multi-component synergy in the invention.
[0026]
[0027] Table 1 As can be seen from Table 1, in the present application, a standing wave field with a resonance frequency of 50-70 Hz is generated by using the acoustic resonance mixing device, and an acceleration of 5-100 g (1 g = 9.8 m / s²) can be set, so as to apply acoustic flow to multi-component materials of different materials, densities and properties (such as high-density, high-thermal / electrical-conductivity single-walled carbon nanotubes, low-density, insulating thermoplastic resin powder, high-density glass fiber / carbon fiber and spherical nanometer silicon dioxide), and the whole material is fully fluidized. This resonance enables energy superposition and mechanical vibration to drive the interaction between particles, realizing rapid and uniform mixing without damaging the material structure. In the composite carbon nanotube / resin composite material, the filling amount of single-walled carbon nanotubes can reach 0.5-5 wt%, the filling amount of glass fiber can reach 1-10 wt%, the filling amount of carbon fiber can reach 0.5-5 wt%, and the filling amount of spherical nanometer silicon dioxide can reach 0.1-2 wt%, the dispersion uniformity is >96% (no obvious agglomeration is observed by SEM), the mechanical properties are significantly improved (tensile strength >90 MPa, modulus >4 GPa), the thermal conductivity is excellent (thermal conductivity >0.5 W / m·K), and the anti-static performance is outstanding (surface resistivity is reduced by 7-10 orders of magnitude). Among them, (1) SWCNTs can provide excellent mechanical reinforcement effect (tensile strength hundreds of GPa), electrical and thermal conductivity (thermal conductivity 2000-6000 W / m·K, high electrical conductivity) and anti-static characteristics, and by forming a continuous conductive network and a thermal conduction path in the matrix, the overall strength, thermal conduction efficiency and surface resistivity can be improved to prevent static accumulation. (2) The thermoplastic resin powder as the matrix phase has good mechanical toughness, forming processability and insulation characteristics, supports extrusion molding process, and can utilize acoustic resonance to induce surface micro-vibration and interface activation to promote infiltration and fusion with fillers. (3) Glass fiber can improve mechanical strength, heat resistance and rigidity, and by forming a fiber reinforced network to improve stress transfer and fatigue resistance, acoustic resonance is used to realize uniform mixing of materials with a density difference of 10-50%, avoiding random impact and damage caused by traditional stirring. (4) Carbon fiber can improve thermal conductivity and rigidity, and by constructing a thermal conduction path to reduce interfacial thermal resistance, it can also assist the conductive network to enhance the anti-static characteristics, and by utilizing the standing wave field to drive random collisions between particles, high filling uniform dispersion is realized. (5) Spherical nanometer silicon dioxide as an interface modifier (particle size 100-200 nm, surface can be treated by silane coupling agent), can promote filler dispersion and interface combination, increase powder flowability and provide shear force to solve agglomeration through its spherical structure, form an optimized layer to reduce thermal resistance and static risk, utilize acoustic resonance to realize uniform distribution (SEM shows no obvious agglomeration), enhance interface infiltration, avoid environmental risks caused by traditional solution mixing, and improve the purity of the composite material (>99%).In summary, the carbon nanotube / resin composite material can be widely applied in automobile industry (such as heat-resistant parts around the engine, lightweight structural parts), electronic information field (such as electronic shell with high heat dissipation demand, integrated circuit packaging material) and precision machinery field (such as wear-resistant transmission parts), and can meet the comprehensive demand of high-end manufacturing on the material “high strength-high thermal conductivity-anti-static-easy forming”. Meanwhile, the preparation process has strong controllability and high industrialization adaptability, including pretreatment, mixing and post-treatment, and can effectively improve the production efficiency and quality stability of the composite material, and provides technical support for the high performance and low cost industrialization of the high polymer composite material, and has significant economic value and application prospect.
[0028] The application applies acoustic resonance technology to the mixing of multi-density, multi-material and multi-performance materials, avoids the random impact and delamination risk of the traditional mechanical method, generates a precise standing wave through low-frequency resonance (50-70 Hz), and drives particles to redistribute through inter-particle collision, so that the particle movement is completely random, delamination is prevented, selective de-agglomeration and interface fusion are realized; compared with other technical solutions, the application has the advantages of short processing time (<40 minutes), high energy efficiency (consumption <40% of the traditional method), no need to add dispersants (purity >99%), wide application range (can process multi-phase systems with a density difference >30% and strong performance contrast, such as conductive & insulating & reinforcing materials); powerful, simple but covers a wide range of scenarios, supports expansion from laboratory small batches to industrial continuous production, can process high filling amount materials, and improves the performance of composite materials in the fields of automobile lightweight, thermal management and anti-static applications. It should be emphasized that the application also needs to be prepared based on acoustic resonance mixing of all other types of composite materials, which falls within the protection scope of the application.
[0029] The above shows and describes the basic principles and main features of the application and the advantages of the application. It is obvious for those skilled in the art that the application is limited to the details of the above exemplary embodiments, and the application can be realized in other specific forms without departing from the spirit or essential characteristics of the application. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting, and the scope of the application is defined by the appended claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the application.
[0030] Furthermore, it should be understood that, although the specification is described in terms of embodiments, the embodiments do not include only singular implementations, but that the specification can include plural implementations of individual systems, other combined systems, and methods described herein.
Claims
1. Carbon nanotube / resin composite based on acoustic resonance mixing, characterized in that, The single-walled carbon nanotube, glass fiber, carbon fiber, spherical nanosilica and thermoplastic resin powder component; the content of the single-walled carbon nanotube is 0.5-5wt%, the glass fiber is 1-10wt%, the carbon fiber is 0.5-5wt%, the spherical nanosilica is 0.1-2wt%, and the thermoplastic resin powder is 78-97.9wt%; the preparation method of the carbon nanotube / resin composite material based on acoustic resonance mixing includes the following flow, S1: preparing the single-walled carbon nanotube, thermoplastic resin powder, glass fiber, carbon fiber and spherical nanosilica according to the quantity, and modifying and pre-drying the surface of the glass fiber and spherical nanosilica; S2: putting the materials in step S1 into the mixing chamber of the acoustic resonance mixing device, and performing multi-stage acoustic resonance mixing of the materials, the resonance cavity of the resonance mixing device generates a resonance frequency of 50Hz-70Hz and an acceleration of 5-100g, and a standing wave field is formed in the mixing chamber to realize micro-uniform dispersion of the components, and the dispersion uniformity is >96%; S3: after mixing, the material is vacuum degassing device, vacuum degassing, hot pressing equipment hot pressing preforming, vacuum drying equipment drying and double screw extrusion molding, to obtain the carbon nanotube / resin composite material.
2. The carbon nanotube / resin composite based on acoustic resonance mixing according to claim 1, wherein The thermoplastic resin powder is one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer, polymethyl methacrylate, polyamide, polycarbonate, polyformaldehyde, polybutylene terephthalate, polyethylene terephthalate, polyether ether ketone, polyimide, polyphenylene sulfide, polyether sulfone, polytetrafluoroethylene, polysulfone, polymethyl pentene, ethylene-vinyl acetate copolymer, and polyphthalamide, and the density is 1.0g / cm³-1.4g / cm³.
3. The carbon nanotube / resin composite based on acoustic resonance mixing according to claim 1, wherein The single-walled carbon nanotube has a purity of >80%, a diameter of 0.5nm-2nm, a length of 1μm-100μm, and a density of 1g / cm³-1.8g / cm³; the glass fiber has a density of 2g / cm³-2.6g / cm³ and a length of 1mm-10mm; the carbon fiber has a density of 1.2g / cm³-1.9g / cm³ and a length of 0.5mm-5mm; and the spherical nanosilica has a density of 1.6g / cm³-2.3g / cm³ and a particle size of 100nm-200nm.
4. The method of claim 1, wherein the carbon nanotube / resin composite is prepared by the acoustic resonance mixing. In step S1, the surface of the glass fiber and spherical nanosilica is modified by silane coupling agent treatment, the modification is realized by stirring the glass fiber and spherical nanosilica with the silane coupling agent for 20-40 minutes by a stirrer at room temperature, and the pre-drying is performed at a temperature of 75°C-85°C in a drying device for 2-2.5 hours.
5. The method of claim 1, wherein the carbon nanotube / resin composite is prepared by the acoustic resonance mixing. In the multi-stage acoustic resonance mixing of step S2, the first stage is mixed at an acceleration of 30g-80g for 8-12 minutes, and the second stage is mixed at an acceleration of 60g-95g for 2-8 minutes, and the total mixing time is <40 minutes.
6. The method of claim 1, wherein the carbon nanotube / resin composite is prepared by the acoustic resonance mixing. In step S3, the vacuum degree of the vacuum degassing device is -0.1 MPa to -0.2 MPa, the time is 15 minutes to 25 minutes; the pressure of the hot-pressing equipment is 5 MPa to 6 MPa, the temperature is 150°C to 160°C, and the time is 10 minutes to 15 minutes; the drying temperature of the vacuum equipment is 60°C to 65°C, and the drying time is 60 minutes to 70 minutes; the tensile strength of the carbon nanotube / resin composite material is greater than 90 MPa, the Young's modulus is greater than 4 GPa, the thermal conductivity is greater than 0.5 W / m•K, and the surface resistivity is 1.0×10^4 to 1.0×10^9 Ω / sq.
7. The method of claim 1, wherein the carbon nanotube / resin composite is prepared by mixing the carbon nanotubes and the resin in a sound resonance mixing apparatus. In step S2, the applied acoustic resonance mixing equipment includes a resonance cavity, an acoustic wave frequency modulation module, a mixing chamber, a control module and a fixing device, the resonance cavity is installed in the middle of the shell through the fixing device, the acoustic wave frequency modulation module is installed at the lower end of the resonance cavity, the mixing chamber is installed in the resonance cavity, the control module is installed at the front end of the shell, the power output end of the control module and the power input end of the acoustic wave frequency modulation module are connected below the acoustic wave frequency modulation module, the vacuum degassing device is installed at the back of the resonance cavity, the air inlet pipe of the vacuum degassing device and the air outlet pipe at the upper end of the mixing chamber are connected through the pipeline, the front end of the shell has a sealed soundproof door, the sealed door is opened before mixing to put raw materials into the mixing chamber and closed.
8. The method for preparing carbon nanotube / resin composite material based on acoustic resonance mixing according to claim 7, characterized in that, In step S2, under the action of the control module, the acoustic wave frequency modulation module of the applied acoustic resonance mixing equipment can output different frequency signals to the resonance cavity through its own frequency automatic adjuster, the resonance cavity can generate a low-frequency standing wave field acting on the mixing chamber, realizing the acoustic flow and uniform mixing of multi-component raw materials without damaging the physical structure of the materials.
9. The method of claim 8, wherein the carbon nanotube / resin composite is prepared by mixing the carbon nanotube and the resin in a sound resonance field. In step S2, the resonance acoustic wave formed by the low-frequency standing wave field can realize the preferential deagglomeration and interface fusion of raw material components with a density difference greater than 30% under the shearing force of spherical silica, without the need for additional dispersants, and the purity is greater than 99%.
Citation Information
Patent Citations
Carbon nanotube resin-based composite material and preparation method thereof
CN115873272A
Flat glass fiber reinforced single-walled carbon nanotube modified PC composite material and preparation method thereof
CN116948378A
Composite glass fiber high-wear-resistance PES resin and preparation method thereof
CN118546526A
High-thermal-conductivity epoxy resin conductive adhesive containing composite conductive filler and preparation method of high-thermal-conductivity epoxy resin conductive adhesive
CN120682744A